(untitled) (Marketing Journal, 2025)
This article examines the theoretical and practical aspects of ensuring macroeconomic stability and combating inflation. Macroeconomic stability is interpreted as a comprehensive condition that encompasses sustainable economic growth, relative price stability, high employment levels, and a balanced foreign trade sector. Inflation, defined as a general increase in prices, can negatively affect economic activity. The article highlights the importance of economic growth, inflation control, employment generation, and trade balance in maintaining macroeconomic stability. It also explores various anti-inflation strategies, including the central bankʼs monetary policy, government budget policy, price regulation measures, and economic diversification strategies. Based on the findings, the study provides policy recommendations for effective inflation control and maintaining macroeconomic equilibrium.